Ishmael Bernal award for young cinema - Communication Arts-De La Salle University, Manila (Animo Repository, 2001)
Two La Salle alumni, Ana Cristina Ganzon and Janis Piopongco (Communication Arts 2001), received the Ishmael Bernal Award for Young Cinema (Special Citation) for their video documentary titled, Alab, at the 3rd Cinemanila International Film Festival. Awarding ceremonies were held on December 16. Cinemanila International Film Festival was launched in 1999.